Design and Analysis of Chemotherapy and Immunotherapy Drug Scheduling Model for Cancer Tumour Treatment (Dhaka University Journal of Science, 2012)
This paper presents an investigation into a mathematical model of cancer tumour growth and response with chemotherapy and immunotherapy treatments. dOnofrio and co-workers[1-3]developed a model to predict and control cancer tumour growth based on cell functions and effects of chemotherapy and immunotherapy. Several design objectives and constraints were used to obtain optimal drug scheduling. These included (i) maximizing tumour cell killing, (ii) tolerable drug concentration, (iii) tolerable body temperature rise and (iv) normal increase of vasculature cell at the end of treatment regime [1]. This paper, initially, implements the model in a simulation environment and then analyzes it with several drug doses that maximize killing of cancerous cells and increase normal vasculature cells during and after treatment period. Then a number of doses have been designed heuristically to improve aforementioned treatment objectives and to analyze the effects of chemotherapy and immunotherapy further. The designed doses show significant improvement in terms of cancerous cell killing with a normal recovery of vasculature cell after the treatment period. This paper also presents an investigation into parameter sensitivity of the model that shows tumour response with different model parameters and drug doses.DOI: http://dx.doi.org/10.3329/dujs.v60i2.11524 Dhaka Univ. J. Sci. 60(2): 231-237, 2012 (July)